2022
DOI: 10.1007/s11130-022-01028-4
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Structure, and Techno-Functional Characteristics of the Flour, Protein Concentrate, and Protein Isolate from Purslane (Portulaca oleracea L.) Seeds

Abstract: One potential avenue to increase the production of valuable protein ingredients for the food industry is developing vegetable proteins from non-traditional plant sources. In the present study, the composition, structure and techno-functional characteristics of defatted purslane flour (DF), protein concentrate (PC), and protein isolate (AP) were investigated. The results revealed that DF, PC, and PI contained low levels of moisture, ash, and fat. However, there were significant differences (P < 0.05) in prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…WPIK showed flatter and tighter microstructures with strong angles varied from crude, defatted, and autoclaved korma. A similar microstructure was also reported in wheat protein [ 54 ], cottonseed meal [ 55 ], protein isolate (PI) of Purslane seeds and ultra sound pretreated quinoa protein [ 56 , 57 ]. The smooth surface of WPIK may be due to the higher content of protein [ 58 ] and the alkali extraction process [ 59 ].…”
Section: Resultssupporting
confidence: 69%
“…WPIK showed flatter and tighter microstructures with strong angles varied from crude, defatted, and autoclaved korma. A similar microstructure was also reported in wheat protein [ 54 ], cottonseed meal [ 55 ], protein isolate (PI) of Purslane seeds and ultra sound pretreated quinoa protein [ 56 , 57 ]. The smooth surface of WPIK may be due to the higher content of protein [ 58 ] and the alkali extraction process [ 59 ].…”
Section: Resultssupporting
confidence: 69%
“…Sowing date and harvesting are two agronomic practices that may have an impact on yield and quality of the final product. Considering the short growth cycle of the species, sowing can take place on various dates from early May to mid-June, as soon as the temperature requirements for germination are fulfilled, and even more than one cropping is possible within the same growing period [ 28 , 38 , 88 ], while plant density may also affect biomass yield [ 95 , 96 ]. The sowing of seeds with the existing sowing machines is troublesome due to the small size of seeds, while seed pelleting would significantly increase seed and crop production cost.…”
Section: Cultivation Practicesmentioning
confidence: 99%
“…The use of purslane extract in edible packaging films also showed promising results against the microbiological and oxidative damage of sausages, while similar effects were reported by Pratiwi et al [ 123 ] for the packaging of mozzarella cheese. Moreover, Rayan et al [ 96 ] suggested the development of novel proteins from purslane seed flour and its incorporation in food proteins, while Delvarianzadeh et al [ 124 ] reported the use of purslane powder in the preparation of voluminous bread. The use of purslane powder obtained from stems and stalks was also evaluated for the biofortification of durum wheat pasta and wheat bread with omega-3 fatty acids by Melilli et al [ 125 , 126 ], respectively; while Santiago-Saenz et al [ 127 ] suggested the use of mixtures of dried edible parts of various wild edible plants, including purslane, in the preparation of food supplements and food products.…”
Section: Future Prospects and Conclusionary Remarksmentioning
confidence: 99%
“…Tapioca flour will be substituted with purslane flour (Portulaca oleracea L.) to improve the functional properties of nutrients in meatballs. The use of purslane flour is based on its relatively high protein content (32.90%), with a complete content of essential amino acids, but has a low-fat content (1.88%) (Rayan et al 2023). Purslane is rich in omega-3 (59.87%) and omega-6 (16.99%) dry matter (DM) (Udin et al 2014), which are functional.…”
mentioning
confidence: 99%
“…fat, and ash on purslane flour. According toRayan et al (2023), purslane flour contains 8.09% water, 32.9% protein, 1.88% fat, and 5.84% ash. The high ash content in purslane flour is caused by the content of potassium, magnesium, calcium, phosphorus, and iron, but the most abundant is potassium(Srivastava et al 2023).…”
mentioning
confidence: 99%